Study and Application of Mutation in Crop Improvement - Safi, Mohammad Taheb (Journal of Natural Sciences – Kabul University, 2021)
Mutagenesis is the process through which sudden heritable changes occur in the genetic information of an organism, not caused by genetic segregation or recombination, but induced by chemical, physical, or biological agents. Mutation breeding is the purposeful application of mutations for crop improvement. Unlike hybridization and selection, mutation breeding has the advantage of improving a defect in an otherwise elite cultivar without losing its agronomic and quality characteristics. Mutation is the only straightforward alternative for improving seedless crops. Mutations occur naturally in all animals and plants, but induced mutations involve the use of X-rays and chemicals. Mutation-assisted plant breeding plays a crucial role in generating genetic diversity, producing high-yielding varieties, shortening flowering and harvesting periods, and increasing resistance to biotic and abiotic stresses.